Economic Regulation Volatility and Resource Rent: Moderating Effect of the Growth of the Financial Sector in the SADC Countries - Aliamutu, Kansilembo; Nzuza, Zwelihle Wiseman (Journal of Ecohumanism, 2025)
This study examines the moderating effect of financial growth on the relationship between economic regulation volatility and resource rents using 2013–2023 SADC data with FMOLS and DOLS methods. The study tested three hypotheses. The first hypothesis tested whether economic regulation volatility has a significant negative effect on resource rents. The second hypothesis examined whether financial growth has a positive and significant impact on resource rents, while the third hypothesis investigated whether financial growth moderates the relationship between economic regulation volatility and resource rents. Findings reveal that economic regulation volatility significantly reduces resource rents (coefficient: -0.622), while financial growth positively impacts resource rents (coefficient: 0.096) and moderates the ERV-RRT relationship (coefficient: 0.199), all at a 1% accuracy level. The negative effect of economic regulation volatility on resource rents likely stems from heightened regulatory volatility, creating uncertainty around government decisions. The research reveals complex economic dynamics within the SADC countries and emphasizes the important role of financial growth in reducing the negative effects of economic regulation volatility on resource rents.